Analyzing The Impact of Human Development Index, Inflation, And Unemployment on Poverty Levels in Jambi Province - Afriwan, Afriwan; Putra, Adi; Fahmi, Ali (Jurnal Prajaiswara, 2025)
Introduction/Main Objective: This study aims to analyze the influence of the Human Development Index (HDI), inflation, and unemployment rate on the number of poor people in Jambi Province. Poverty is a strategic issue that reflects development inequality and low community welfare. Background of the Problem: Although HDI in Jambi Province has shown consistent improvement from 2014 to 2023, poverty rates have not decreased significantly. Meanwhile, fluctuations in inflation and unemployment remain key factors influencing poverty dynamics in the region. Novelty: The novelty of this research lies in the integration of three macroeconomic variables into a single empirical model focused on Jambi Province over a consistent time period. This provides a more detailed and region-specific analysis that has not been extensively explored in previous studies. Findings/Results: The analysis reveals that HDI has a significant negative effect on poverty, indicating that improved human development reduces poverty levels. Conversely, inflation and unemployment both have significant positive effects on poverty, suggesting that increases in these variables tend to raise poverty rates.Conclusion: It is recommended that the Jambi provincial government continue improving human capital through better education and health services, while also managing inflation and expanding employment opportunities. Furthermore, supportive policies for the development of MSMEs are essential to absorb labor and boost household income.